The effect of a running program on the weight and VO2max of U19 football players - study carried out by the Polar system during the interruption period caused by the Covid-19 pandemic. - Kherrachi , Toufik; Akezouh, Salim (sports creativity, 2025)
The aim of this study was to examine the effect of a running program, using the POLAR system, on the weight and VO2max of players affected by the unexpected shutdown imposed by the Coronavirus pandemic. Ten (10) U19 football players from Mouloudia Club d’Alger (MCA) were randomly selected and followed a two (2) month running program during the shutdown period imposed by the COVID-19 pandemic. The group refrained from any structured physical activity for two and a half months (from the start of the lockdown) before beginning a running program with the POLAR system (Polar v800 watch, H7 heart rate monitor) for eight weeks. Anthropometric measurements (weight, height, and BMI) and an IR1 yo-yo intermittent recovery test were performed before and after the program. Our results showed that the running program performed by the POLAR system resulted in weight loss and an improvement in maximum oxygen consumption (VO2max).